Technology for processing carbon-containing waste - Sitdikov, Zh.Zh.; Messerle, V.Ye.; Ustimenko, A.B.; Baimuldin, R.V. (Recent Contributions to Physics, 2018)
Today, population growth on the planet and the intensification of human activities in connection with the scientific and technological revolution inevitably leads to a sharp increase in the anthropogenic impact on the environment. Human impact exceeds the regeneration capabilities of the natural environment. This article is review of technologies for processing of different waste. Initially, all kinds of waste sorting on secondary raw materials (metal, glass, paper, plastics and polymers) and utilized organic part. Sorting is subjected to industrial and municipal waste that can be identified. However, there are a number of hazardous wastes that are not subject to sorting. These include biomedical and radioactive waste. Modern technologies make it possible not only to destroy hazardous waste, but also to get the material and energy resources. The most promising of them is high-temperature plasma processing of waste. It is practically the only waste processing technology that guarantees the destruction of dangerous biological, biochemical, chemical products and super toxicants - benz(a)pyrene, furans, dioxins and dioxin-like substances. Plasma gasification of carbonaceous waste produces high-energy and environmentally friendly synthesis gas. Synthesis gas can be used as an energy gas, a raw reagent for the synthesis of synthetic liquid fuels and an economical energy carrier for modern power generators. The remaining ash is processed into granular slag or ceramic tile.